Ceftazidime-Avibactam as a Salvage Treatment for Severely Infected Immunosuppressed Children - Zhu L; Hu Q; Liu L; Ye S (Dove Medical Press, 2024)
Lvchang Zhu,1,* Qiongyao Hu,2,* Lijun Liu,1 Sheng Ye1 1Department of General Intensive Care Unit, Children's Hospital, Zhejiang University School of Medicine, National Clinical Research Center for Child Health, Hangzhou City, Zhejiang Province, People's Republic of China; 2Department of Clinical Nutrition, Children's Hospital, Zhejiang University School of Medicine, National Clinical Research Center for Child Health, Hangzhou City, Zhejiang Province, People's Republic of China*These authors contributed equally to this workCorrespondence: Sheng Ye, Email Yeshengchina@zju.edu.cnBackground: Multidrug-resistant Gram-negative bacteria (MDR-GNB) are becoming increasingly common around the world, with carbapenems frequently serving as a last resort but being threatened by the growing incidence of carbapenemase-producing bacteria. Ceftazidime-avibactam (CAZ/AVI) is a potential agent against MDR-GNB but with limited clinical experience, particularly in critically ill immunosuppressed children.Methods: This study analyzed the use of CAZ/AVI as salvage treatment in severely infected immunosuppressed children from September 2019 to July 2022. Patients with confirmed GNB infection who received CAZ/AVI were matched with patients who received other antibiotics.Results: Twenty-five critically ill immunosuppressed children treated with CAZ/AVI were included. The majority had hematologic diseases. All patients presented with sepsis in all 30 courses. Septic shock presented in 36.7% of these courses. The primary sites of infection included bloodstream infection (20.0%), skin and skin structure infection (20.0%), intra-abdominal infection (13.3%) and hospital-acquired pneumonia (10.0%). Twelve of the 25 (48.0%) patients had positive microbiological cultures, mainly Pseudomonas aeruginosa and Klebsiella pneumoniae, including 5 carbapenem-resistant GNB-infected cases. Fifteen (50.0%) courses presented clinical improvement. For the initial course of each patient, the clinical response rate of the GNB recovered group was significantly higher than that of the group without GNB recovery (66.7% vs 23.1%, P = 0.047). The 14-day and 30-day mortality rates were 24.0% and 28.0%, respectively, which were significantly correlated with the absence of GNB recovery (P = 0.004 and 0.024, respectively) and hospital-acquired pneumonia as the primary site of infection (P = 0.001 and 0.006, respectively). There was no significant difference in major outcomes between patients who received CAZ/AVI and matched patients who received other antibiotics.Conclusion: CAZ/AVI could be considered a salvage strategy for immunosuppressed children with confirmed GNB infection. Caution should be taken when CAZ/AVI is applied to these patients in the absence of GNB recovery.Keywords: gram-negative bacteria, hematological disease, hematopoietic stem cell transplantation, adverse events